Thinking to transform : facilitating reflection in leadership learning. - Volpe White, Jillian M.; Guthrie, Kathy L.; Torres, Maritza (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2020)
"Through courses, internships, community engagement, social organizations, and daily interactions with others, every day we accumulate experiences; however, learning does not happen through experience but from reflection on experiences. This manual provides guidance for facilitating reflection in leadership learning and features over 50 activities from 52 reflective leadership educators. Guided by a framework for reflection in leadership learning, we focus on six methods for reflection: contemplative, creative, digital, discussion, narrative, and written. Through prioritizing time, holding space, and asking questions that challenge assumptions, educators facilitate reflection in leadership learning. This intentional focus on making meaning of leadership processes enhances the capacity of learners to work collaboratively for change"-- Provided by publisher.
Keywords: Educational leadership -- Study and teaching -- Activity programs.; Reflective learning.; Education -- Leadership.; Educational administration and organization.; Educational strategies and policy.; elektronické knihy; electronic books